THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE MEDIATED BY WORK MOTIVATION IN HOSPITALS. YPK MANDIRI - Aprian Pamungkas, Yosua; M.Ali Iqbal; Ahmad Badawi Saluy (Dinasti Publisher, 2022)
This study aims to discover and describe the impact of transformational leadership on the work environment on performance with work motivation. The number of respondents who participated was 100 people. All speakers are employees of YPK Mandiri Hospital. This research was conducted using tools in the form of questionnaires and quantitative methods. With the help of the SmartPLS program, the research data was analyzed using minor partial squared analysis technology. The results of the research analysis obtained data, namely: transformational leadership affects work motivation; the work environment affects work motivation; transformational leadership affects employee performance; the work environment does not affect employee performance; work motivation: Has an impact on employee performance; motivation can moderate the effect of the work environment on performance